PENGARUH GAME BOARD TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 4-5 TAHUN DI TK TUNAS KEMUNING DESA KEMUNING MUDA KECAMATAN BUNGARAYA KABUPATEN SIAK - Desi Rahmawati; Zulkifli N; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of field observations on the ability to recognize the concept of number of students have not developed optimally. So it is necessary to apply Game Board. The purpose of this study was to examine the effect of Game Board on the abilityto recognize concept number of children aged 4-5 years. The research was conducted at TK Tunas Kemuning Desa Kemuning Muda of Siak district. The research used experimental method with one group pre-Test post-Test design with 15 samples. The data collection technique used is an observation sheet to record about the activities occurring during the treatment given. Data analisis technique using t-test by using the SPSS program of Windows ver. 20 from the results of data analysis obtained t count of 12.773 bigger than t table = 2.145 with sig 0.000 < 0.05. It can be concluded that there are differences in the ability to recognize concept of significant numbers before and after the Game Board implementation. Based on the hypothesis test results obtained there is the influence of Game Board on the ability to recognize the concept of number of children aged 4-5 years at 57.82 %Key Words : Know the Concepts of Numbers, Game Board